Adherence Isoniazid Preventive Therapy Use Among Family Members of Patients with Tuberculosis: Systematic Literature Review - Siagian, Nur Aima; Putri, Yossie Susanti Eka; Chandra, Yudi Ariesta; Daulima, Novy H.C (Jurnal Locus Penelitian dan Pengabdian, 2025)
In countries such as Indonesia, Tuberkulosis (TB) is one of the most prevalent infectious diseases in the world. Active tuberculosis patients can prevent the evolution of tuberculosis through isoniazid preventive therapy (IPT). However, adherence to this regimen is particularly low among family members of tuberculosis patients. This study[A1] [A2] aims to explore the factors influencing compliance with IPT among family members of tuberculosis patients and assess the impact of family and community support on compliance. Various studies relating to IPT adherence were reviewed, especially in high TB burden areas such as Greater Jakarta. Socioeconomic status and education level, as well as awareness regarding TB prevention, were found to influence the level of adherence of respondents. Community and family involvement and education on TB, social stigma, and how to overcome it were found to significantly help in controlling medication adherence and the spread/transmission of TB. The results of this study support the strengthening of initiatives aimed at TB control, especially in households with high risk of TB exposure.